Corporate Social Responsibility and Community Development Surrounding a Mining Company, 2018 - Carlín Villarreal, Víctor Martin (2023)
In countries where mining activity is one of the most important sources of income, there is a constant interest in identifying those management practices that make it possible to satisfy the needs and perspectives of the population, among which corporate social responsibility deserves special mention. The purpose of this research was to establish the correlation between corporate social responsibility and community development in the environment surrounding a mining company. This was a non-experimental research study with a correlational design and non-probabilistic sampling; the sample consisted of the company’s workers and the local inhabitants. The technique used was the survey, and the questionnaire was used as the data collection instrument, which met the criteria of validity and reliability (Cronbach’s alpha coefficient = 0.833). Social responsibility dimensions such as “ethics” (information transparency), “sustainability” (participation and mutual benefit), “human capital” (human resources management and occupational safety) and “safety” (change adjustment and impact management) stand out from the instrument, as they are specific to the reality of the study. From the results, it is evident that there is a high correlation (r = 0.964) between the two research variables, social responsibility and community development, due to the high and significant correlation between the two.